IMPACT OF MINERALFORMATION ON RESTORATION OF THE SOIL STRUCTURE IN NAKHCHIVAN AR AND GEOGRAPHICAL SPREADING LEGITIMACY. - Aliyev, RAE. Z.H. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2017)
The silt fractions have a great impact in soil structural formation. If the soil forming rocks don’t disturb, crush and weather, the soil forming processes on them occur weakly, the organic substances cause formation of the loamy stratums without completely turning. This mostly influences the initial soil forming layers. The reproduction minerals in these soils cause initial minerals majority by occurring weakly. If these processes occur quickly then they cause a gradual increase of the reproduction minerals and reduction of the initial minerals. The heights of the zones where the geographical spreading of such stratums is situated depend on levels.